Impact of Work Environment Noise on Cardiovascular Conditions: A Study of Blood Pressure and Heart Rate in Workers (Heavy Equipment Manufacturing) in East Java - Permana Adhenan Samudra; Rachmaniyah; Putri Arida Ipmawati; Suprijandani; Ambarwati; Anni Ilma Rosyidah; Wisnu Prayogo (Indonesian Association Environmental Health of West Kalimantan, 2024)
Workplace noise is one of the physical factors that is often overlooked, although long-term exposure can have serious impacts on cardiovascular health. In workers exposed to noise, blood pressure and heart rate often increase as the body's response to physical stress. This physiological mechanism triggered by prolonged noise can result in an increased risk of cardiovascular disorders, including hypertension and heart rhythm disorders. The purpose of this study was to analyze the effect of noise on increasing blood pressure and heart rate in workers in the workshop area, especially the dynotest room. This type of research is observational with a cross-sectional research design. Conducted in December - May 2024 with the object of research on workers exposed to noise in the workshop area, especially the dynotest room. Data were analyzed using the Logistic Regression test. The total sample was 40 workers in the workshop area and dynotest room. Data were collected from observations, room noise measurements, blood pressure, and heart rate. Based on the results of the study, the average results for the dynotest area were 83.5 dBA, while for the dynotest room, the average results were 117.8 dBA. The results of statistical tests of blood pressure and pulse rate in workers obtained a sig value = 0.001. These results indicate an increase in blood pressure and pulse rate due to noise. It is recommended for the Company to monitor workers to find out the disorders caused by noise.